Medicinal Plant and Their Bioactive Phytochemicals in the Treatment of Recurrent Aphthous Ulcers: A Review of Clinical Trials - Heydarpour, Fatemeh; Abasabadi, Masoomeh; Shahpiri, Zahra; Vaziri, Siavash; Nazari, Hesam Aldin; Najafi, Fariba; Mirzaei, Maryam; Farzaei, Mohammad Hosein (Pharmacognosy Reviews)
Considering the unclear etiology of recurrent aphthous ulcers (RAUs), the clinical management of RAU is based on no optimal therapeutic approach. The current study aimed to review the clinical trials on the effectiveness of medicinal plants and their active phytochemicals in the treatment of RAU. Five databases including PubMed, Science Direct, Web of Science, Scopus, and Cochrane Library were searched for retrieving all the relevant clinical trials. The results indicate that a wide range of scientific evidence has approved the therapeutic benefits of natural medicaments in the management of RAU, including Satureja khuzistanica, Aloe vera, Myrrh, Glycyrrhiza glabra, Alchemilla vulgaris, Myrtus communis, Melissa officinalis, Rhizophora mangle, Chamomile, Rosa damascena, Nicotiana tabacum, Punica granatum, Ageratina pichinchensis, Norwegian LongoVital, Lavender oil, and Perilla oil that are known anti‑aphthous medical plants. Berberine and acemannan are bioactive substances with diverse pharmacological and therapeutic benefits in patients with aphthous, which made them as the promising alternatives for new pharmacological drugs. This review provides evidence that medicinal plants can be considered as future pharmaceutical drugs or adjuvant treatment with conventional therapeutic approaches to improve their efficacy and alleviate the side effects in the management of RAU. Further clinical studies are also necessary to confirm the efficacy and safety of plant‑derived natural products with potential effects in treating RAU.
Keywords: Herbs; mouth ulcers; phytochemical compounds; recurrent aphthous ulcer